2017
DOI: 10.15419/jmri.4
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of New Risk Factors for causing Hypertension

Abstract: The major risk factors which we have been hearing since decades for causing hypertension are high salt diet, obesity, hyperlipidaemia, age, race, consuming tobacco, sedentary lifestyle, stress, drinking too much alcohol etc. However, there are many studies which shows that sugar, fats and low vitamin d levels are equally responsible for causing hypertension. The article will put forward some interesting points to show that sugars, fats and vitamin d levels equally play an important role in causing hypertension. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…[ 14 ]. Furthermore, high fat and sugar levels may lead to HTN as well and subsequently preeclampsia [ 21 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ]. Furthermore, high fat and sugar levels may lead to HTN as well and subsequently preeclampsia [ 21 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mehta suggested that low levels of Vitamin D, along with sugar and fats, should be considered as new risk factors in causing hypertension [ 14 ]. This article will bring forward the importance of Vitamin D and its role in maintaining blood pressure levels.…”
Section: Introductionmentioning
confidence: 99%
“…Some proposed mechanisms are obesity [44], high dietary glycemic load, insulin resistance, β-cell dysfunction, and inflammation [9]. The high content of rapidly absorbed carbohydrates such as sucrose and highfructose corn syrup in SSBs, in conjunction with the large volume consumed, also may lead to hypertension [10], visceral and ectopic adipose tissue accumulation [11,12], and hepatic lipogenesis elevation [13]. Increased uric acid production and lower levels of the vasodilator Nitric Oxide resulted from sugar are other possible factors [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Some surveys claimed that sugary beverages contribute to obesity and CVD. They are also supposed to increase insulin resistance, inflammation [9], hypertension [10], adiposity [11,12], and lipogenesis [13,14]. The Framingham Offspring Study demonstrated increased incidence of hypertension after four years consumption of ≥1 serving soft drink/day by 22% [15] and also higher incidences of hypertriglyceridemia and low level of high-density lipoprotein cholesterol (HDL-C) compared with non-consumers [15].…”
Section: Introductionmentioning
confidence: 99%